Factors associated with efficacy of first-generation epidermal growth factor receptor tyrosine kinase inhibitors in non-small-cell lung cancer - Shaohua Cui; Liyan Jiang (Tumor Biology)
The finding of epidermal growth factor receptor tyrosine kinase inhibitors, which reflects a classical process of translational research, is a critical milestone for non-small-cell lung cancer treatment. Currently, epidermal growth factor receptor tyrosine kinase inhibitors are recommended as first-line therapy for non-small-cell lung cancer patients harboring epidermal growth factor receptor–sensitive mutations. The status of epidermal growth factor receptor mutation is widely acknowledged as superior to other clinical factors, such as smoking, gender, and histological types for predicting the response to epidermal growth factor receptor tyrosine kinase inhibitors. However, recent studies have shown that the efficacy might differ in patients with the same epidermal growth factor receptor–sensitive mutations, highlighting the need to investigate the putative factors related to the efficacy of epidermal growth factor receptor tyrosine kinase inhibitors. This article reviews the factors associated with clinical efficacy of first-generation epidermal growth factor receptor tyrosine kinase inhibitors, such as gefitinib and erlotinib, and analyzes their potential implications with respect to clinical application. In addition, new findings related to clinical practice with respect to epidermal growth factor receptor tyrosine kinase inhibitors efficacy were summarized in this article.